Comparison of the effectivity of handrubbing and handwashing on the number of bacterial colonization on clinical students at the Department of Oral and Maxillofacial Surgery, Faculty of Dentistry, Universitas Sumatera Utara March-May 2018 - Ahyar Riza; Abdullah Oes; Hendry Rusdy; Khairun Nisah (DiscoverSys Inc., 2019)
Objective: To compare handrubbing and handwashing effectivity on total bacteria count on clinical students at the Department of Oral and Maxillofacial Surgery, Faculty of Dentistry, Universitas Sumatera Utara March - May 2018.Material andÂ Methods: This is an experimental study with pre-test pos-ttest group design carried out by purposive sampling technique. In this study, sample were divided into 2 groups and each consist of 20 people which are handrubbing and handwashing groups. Bacterial samples were obtained by placing the right hand in a container that contain NaCl 0.9% solution for 1 minute. Samples were then grown in nutrient agar plate and incubated at 37Â°C for 48 hours. The culture results were calculated using the colony counter tool.Results: There is a significant difference before and after handrubbing with significance 0.00 (P<0.05) and before and after handwashing with significance 0.001 (p<0.05) in reducing bacterial colonization in hand with. However, there is no significant association between handrubbing and handwashing method in reducing the number of bacterial colonization with a significance number of 0.892 (p> 0.05).Conclusion: There is no significant differences between handrubbing and handwashing in reducing the number of bacterial colonization.